Deep clinicopathological phenotyping identifies a previously unrecognized pathogenic EMD splice variant. Issue 10 (15th September 2021) - Calame, Daniel G.; Fatih, Jawid M.; Herman, Isabella; Coban‐Akdemir, Zeynep; Du, Haowei; Mitani, Tadahiro; Jhangiani, Shalini N.; Marafi, Dana; Gibbs, Richard A.; Posey, Jennifer E.; Mehta, Vidya P.; Mohila, Carrie A.; et al.
Abstract: Exome sequencing (ES) has revolutionized rare disease management, yet only 25%–30% of patients receive a molecular diagnosis. A limiting factor is the quality of available phenotypic data. Here, we describe how deep clinicopathological phenotyping yielded a molecular diagnosis for a 19‐year‐old proband with muscular dystrophy and negative clinical ES. Deep phenotypic analysis identified two critical data points: (1) the absence of emerin protein in muscle biopsy and (2) clinical features consistent with Emery‐Dreifuss muscular dystrophy. Sequencing data analysis uncovered an ultra‐rare, intronic variant in EMD, the gene encoding emerin. The variant, NM_000117.3: c.188‐6A > G, is predicted to impact splicing by in silico tools. This case thus illustrates how better integration of clinicopathologic data into ES analysis can enhance diagnostic yield with implications for clinical practice.